Homestead survival : an insider's guide to your great escape - Raney, Marty (TarcherPerigee, Penguin Random House LLC, 2022)
"A practical guide to self-sufficient and sustainable living from the star of Homestead Rescue. Do you wish for a more resilient, sustainable, and empowered way of providing for your family in uncertain times? Are you worried about unreliable power grids, uncertain water supplies, or overly complex food chains? Veteran homesteader and star of the Discovery Channel's Homestead Rescue Marty Raney shares a big-picture vision of how ordinary families can become radically resilient homesteaders: powering, feeding, and caring for themselves through their own efforts, and on their own land"--